Irans risikable isolation: Sanktionerne set fra Teheran - Janne Bjerre Christensen (Danish Institute for International Studies (DIIS), 2013)
– Iran is now subjected to the harshest economic sanctions ever imposed on any country in the world. This report discusses if and how these sanctions work, first by analysing their intended purposes and how the many phases and layers of sanctions imposed by the USA, the EU and the UN Security Council have created an almost impenetrable, escalating sanctions regime against Iran. Secondly, the report illustrates how the sanctions are experienced, debated and received in Iran, and what direct and indirect consequences the sanctions have on Iran's nuclear program, the country's financial crisis, social conditions and the upcoming presidential election in June 2013. The conclusion is that the sanctions do work, but not according to their intentions. The sanctions are contributing to changing Iran: The external pressure creates further tensions and fractions on the domestic political scene; the market moves from the West to the East, and people are subjected to a humanitarian crisis. But the sanctions have not limited Iran's nuclear program; it has only been further developed during the last seven years. Therefore, there is still a considerable risk that the increasing isolation of Iran in a worst case scenario can lead to a military confrontation.
Keywords: 300